2012
DOI: 10.1002/pen.23168
|View full text |Cite
|
Sign up to set email alerts
|

Rotational molding of polyethylene composites based on agave fibers

Abstract: In this study, agave fiber/linear medium density polyethylene composites were manufactured by rotational molding. A laboratory scale biaxial machine was used, where the internal air temperature during the processing cycle was measured. Two sizes of agave fibers (50 and 100 mesh) were used separately and mixed together (50/50) at concentrations varying between 0 and 15 wt%. The initial mixtures were obtained by dry blending, rotomolded under different operation conditions (oven temperature, processing cycle tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
71
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(75 citation statements)
references
References 28 publications
(35 reference statements)
4
71
0
Order By: Relevance
“…For R‐BCs at 40 wt.%, the strength decreased by 90% (from 59 MPa for PLA to 6 MPa), and 53% (from 60 MPa for PLA to 29 MPa) for 40 wt.% CM‐BCs. Rotomolded composites presented lower tensile strengths due to their higher porosity limiting adequate stress transfer as also reported for PLA composites reinforced with agave, coir and pine, sisal, bamboo, and kenaf, as well as in polyolefin composites and foams …”
Section: Resultsmentioning
confidence: 99%
“…For R‐BCs at 40 wt.%, the strength decreased by 90% (from 59 MPa for PLA to 6 MPa), and 53% (from 60 MPa for PLA to 29 MPa) for 40 wt.% CM‐BCs. Rotomolded composites presented lower tensile strengths due to their higher porosity limiting adequate stress transfer as also reported for PLA composites reinforced with agave, coir and pine, sisal, bamboo, and kenaf, as well as in polyolefin composites and foams …”
Section: Resultsmentioning
confidence: 99%
“…In addition, with fiber surface treatments (alkali treatment with NaOH and maleated polyethylene (MAPE)), mechanical properties were improved (35% for flexural modulus), and it was also possible to introduce up to 25 wt% of fibers. 13 Also, López-Bañuelos et al 14 investigated the effect of agave fibers on LMDPE, while Wang et al 15 studied the influence of various fiber treatments (benzoylation, silane, peroxide) and their reinforcing effects on different matrices (LLDPE, HDPE, LLDPE, and HDPE) for compounds prepared by twin-screw extrusion. Jayaraman et al 16 investigated the effect of sisal fibers to reinforce LMDPE, while Ortega et al 17 studied the effect of banana and abaca fibers to reinforce metallocene polyethylene.…”
Section: Rotomolding Of Natural Fiber Compositesmentioning
confidence: 99%
“…They concluded that the optimum PIAT depends on several parameters such as the polymer grade, the nature of the stabilizer, the type of atmosphere inside the mold, and any parameter affecting heat transfer rates. IAT was also used to determine the effect of particle size and shape on the sintering stage , or the effect of natural fibers in rotomolding composites . Furthermore, the reduction of cycle times has been monitored by IAT, applying pressure inside the mold or using molds with extended surfaces of different geometries .…”
Section: Introductionmentioning
confidence: 99%
“…In the most cases it is very important to know the PIAT to avoid material degradation. For example, in the case of composites with natural fiber the PIAT should not exceed the degradation temperature of the fiber . In the polymer foaming process, the PIAT will be determinant to ensure the complete decomposition of the foaming agent .…”
Section: Introductionmentioning
confidence: 99%